Relationships between Physical Activity and Balance Performance among Children with Autism Spectrum Disorder - Sedigheh Khajeaflaton Mofrad; Forough ShafaeianFard; Tayebeh Baniasadi (Journal of Modern Psychology, 2022)
It has been shown that physical activity (PA) is related to motor proficiency in children. Nevertheless, relationships between PA and balance performance among children with autism spectrum disorders (ASD) has been rarely examined. Hence, the aim of this study was to examine the relationships between PA and static and dynamic balance performance among children with ASD. The method used in this study was correlational. Eighty children with ASD (range age between 8 to 14 years old, average 11.51 years old) attended in special schools participated in this study. PA was measured using Physical Activity Questionnaire for Older Children (PAQ-C). Static and dynamic balance tests were used to measure balance performance. Pearson correlation test and regression analysis were used for data analysis. Children with ASD had low amount of PA and balance performance. PA was significantly and directly associated with static and dynamic balance performance. In addition, PA has significantly and directly predicted both static and dynamic balance performance. PA plays a very important role in the motor proficiency in children with ASD. Hence, there is a need for targeted strategies and interventions to increase the level of PA in this population.